PENGARUH KUALITAS JASA SISTEM INFORMASI TERHADAP KEPUASAN DAN PERILAKU PARA PEMAKAI DALAM PENGEMBANGAN SISTEM INFORMASI - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT An increasing number of organizations have developed and implemented information systems, hoping to improve the information systems effectiveness and user satisfaction. The information systems unit now includes a significant service component. Servicequality, an instrument developed by the marketing area, is offered as a possible measure of information systems service quality. Service quality measures service dimensions of tangibles, reliability, responsiveness, assurance, and empathy that compare the expected and perceived measurements. This study was undetaken in order to further examine the effect of service quality to user satisfaction and user behaviour in the information systems development. The data is collected with survey method. The responses of 103 respondents from a cross-section of departements in Indonesia companies to a questionaire survey designed to measure the variables, were analysed using t-test and AMOS 4.0 program. Beside that, factor analysis and cronbach alpha were conducted to examine the validity and reliability of instrument. There are several findings of this study. First, service quality instrument is reliable and valid as a measuring effectiveness information systems. But, it is important to reexamine dimension of empathy for future research. Second, the information system effectiveness test from service quality dimension shows that there is a different between unit of information system's expected and perceived service quality. Third, this study is supported effect fo expected service quality to user satisfaction and this study is supported effect of perceived service quality. At last, there is effect of user satisfaction to user behavior in unit of information system. Keywords: service quality user satisfaction â user behavior information system development.